Acute alithiasic cholecystitis - Piñeyro, Alberto; Carriquiry, Luis; Rodríguez, José L. (Cirugía del Uruguay, 1986)
Presented 5 cases of alithiasic acule cholecystitis treated in !he las! two years. Briet review of the subject and, in particular, circumstances under which the'tlisease appeared, symptomatology, complementary exams and most frequent bacteriology.